(untitled) (Conference Zone, 2022)
The characteristics of transition metal-ligand bonds become clear by an analysis of the molecular orbitals of a 3d metal coordinated by six identical ligands in octahedral complexes [ML6]. As the result of the interaction between the metal d and ligand orbitals, bonding, non-bonding and anti-bonding complex molecular orbitals are formed. Generally, the energy levels of the ligand orbitals are lower than those of the metal orbitals, bonding orbitals have more ligand character and non-bonding and anti-bonding orbitals have more metal character.